PENEGAKAN HUKUM TERHADAP PENYALAHGUNAAN PSIKOTROPIKA OLEH PENYANDANG DISABILITAS DI POLRESTA YOGYAKARTA - Anton Prasetya Wijaya; Sigit Herman Binaji; Dhea Piscesa (Fakultas Hukum Universitas Janabadra, 2025)
Abstract This study aims to analyze law enforcement policies against psychotropic abuse by persons with disabilities at the Yogyakarta Police Station and aims to determine the factors causing the use of psychotropic substances among persons with disabilities. The approach used by the author is the legal approach. related to the steps taken by the Yogyakarta Police Narcotics Unit in law enforcement of psychotropic abuse by persons with disabilities by implementing Penal and Non-Penal policies, in addition to using a concept analysis approach (analytical appraisal), and a case approach (case appraisal). The conceptual approach method is carried out to determine the process of resolving existing psychotropic abuse towards legal handling, while the Case approach is to analyze cases involving persons with disabilities who commit psychotropic abuse. The analysis used is qualitative, namely the method of data analysis by grouping and selecting the data obtained from research based on its quality and truth. Factors causing narcotics abuse against persons with disabilities are personality, family, education, environmental and economic factors. In general, the factors that cause people with disabilities to use or abuse psychotropic substances are due to inferiority or lack of confidence and feeling isolated due to physical limitations. Policies and legal remedies in overcoming narcotics abuse consist of penal and non-penal policies, which are either legally processed or rehabilitated. Efforts made by the Yogyakarta Police Narcotics Unit in preventing and dealing with Psychotropics are by means of pre-emptive, preventive and repressive methods.